Kidney donation & transplantation attitudes, beliefs & intention to donate & receive among family members, caregivers or watchers of hemodialysis patients - Crisostomo, Arlene Cabotaje-
RATIONALE: Chronic kidney disease stage V, also known as End Stage Renal Disease is the tenth leading cause of mortality in the Philippines. The accepted best modality of treatment is kidney transplantation. However, a shortage of donors exists. A nationwide local survey on organ donation by the Renal Disease Program among the general population in the year 2000 revealed a 64 percent willingness to be an organ donor. However, in reality there is a great difficulty in convincing people to donate an organ and this reported willingness to donate is not clinically evident. It was recommended that people with higher propensity to be organ donors be prioritized and be considered as a primary target population for organ donation. No study has been done to determine their attitudes, beliefs, and behavioral intention to donate and receive a kidney. OBJECTIVES: To determine the attitudes and beliefs of family members, caregivers, or watchers of hemodialysis patients toward kidney donation and transplantation; and to determine the association between socio-demographic factors and behavioral intentions to donate and receive a kidney using a locally validated questionnaire. DESIGN: Cross-sectional study in two phases, developed and validation of the questionnaire and survey proper. SETTING: Private Outpatient hemodialysis clinic Quezon City, Metro Manila, Philippines. METHODS: The first phase involved a survey of out patient hemodialysis units in Quezon City and Manila, interviews of priests and imams, and the development and validation of the questionnaires with 40 respondents. In the second phase, 200 family members, caregivers, or watchers of hemodialysis patients were asked to complete the self-administered developed in Phase I. SAMPLING: In Phase II, respondents were recruited consecutively as their patients came in for hemodialysis. If the patient had more than one companion or watcher, the respondent was chosen as follows: family member was preferred over the caregiver or the caregiver over the watcher. And for family members, the following order was used: siblings preferred over the children, the children over the parents, the parents over cousins, cousins over uncles/aunts, uncles/aunts over nephews/nieces, nephews/nieces over the spouse. STATISTICAL ANALYSIS: The actual number of patients and percentage of patients for each religion were reported in Phase I. For Phase II, the socio-demographic profile of the subjects was described. Independent T-Test was used to compare the mean attitudes and beliefs of the participants between categorical binary factors. For qualitative factors having more than two categories, one-way Analysis of Variance (ANOVA) was used. For the quantitative factors such as age, duration of care, and annual household income, simple linear regression was used. Results of the above analysis were examined and factors to be included in the multiple linear regression analysis were determined. Multiple regression analysis was done to determine the patients' characteristics that are associated to one's tendency to donate or receive a kidney. All tests were don at a = 0.05, two-tailed.